2002
DOI: 10.1148/radiol.2241011222
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fecal Tagging as a Cleansing Method before CT Colonography: Initial Results—Polyp Detection and Patient Acceptance

Abstract: FT offers the patient a well-tolerated preparation and improves specificity, with improved differentiation of polyps from residual stool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
139
1
12

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(157 citation statements)
references
References 48 publications
5
139
1
12
Order By: Relevance
“…Improvement may result from the use of a less extensive or even "dry" bowel preparation (e.g., Fleet Phospho Soda® the day prior to the study, the use of fecal tagging (3,5,20), etc.) in conjunction with a single breathhold 2D or 3D T1w sequence after distention of the colon with air, covering the entire abdomen in one acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement may result from the use of a less extensive or even "dry" bowel preparation (e.g., Fleet Phospho Soda® the day prior to the study, the use of fecal tagging (3,5,20), etc.) in conjunction with a single breathhold 2D or 3D T1w sequence after distention of the colon with air, covering the entire abdomen in one acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the use of different imaging modalities and parameter settings for virtual colonoscopy, as well as the corresponding detection rate for small tumors and polyps (2)(3)(4)(5)(6). The participation rate of the target population is often neglected, even though all current techniques require a specific preparation protocol that is associated with definite discomfort for the patient (7).…”
mentioning
confidence: 99%
“…It is noteworthy to mention that at present several 3D software packages, including the newer version of the one used in this study, enable the matching of lesions in the prone and supine position. The use of oral contrast agents [17] and scanning with thinner slices [18] are two other measures that may reduce the number of false positive findings. Another explanation for the lower number of small (≤5 mm) false positive results for the primary 2D review may be that small colon wall abnormalities are simply not seen with axial interpretation, and thus not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of other developments, such as use of low dose scan technique [24] or the use of oral or intravenous contrast agents [17,25,26] on the use of primary 3D and 2D review techniques have not been addressed in the present study and remain subjects for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients perceive laxative bowel preparation as the worst aspect of the test 4,5 and the addition of 'faecal tagging' may add additional burden. Quantitative studies of acceptability have found non-laxative preparation to be equivalent or superior to full-laxative preparation in terms of its acceptability [6][7][8][9][10] . However, although non-laxative CTC is likely to be better tolerated, its diagnostic accuracy compared to full-laxative studies is currently uncertain and so this preparation is generally reserved for patients considered unfit for full catharsis 11 .…”
Section: Introductionmentioning
confidence: 99%